Assessment of different combinations of substrate-filter membrane in green roofs. (January 2022) - Carrera, Diego; Lombillo, Ignacio; Carpio-García, Jaime; Blanco, Haydee
Abstract: Many strategies focus on supporting green infrastructure as a mechanism to contribute to economic growth while safeguarding the environment. However, the effectiveness and performance of green roofs depend on the composition and properties of layers, and their interaction, which has received little attention. Therefore, the article aims to establish the suitability of nine different combinations of substrate-geotextile (filter membrane) in green roofs. This study is novel as it introduces the global performance of different green roof configurations, including: common material frequently used in green roof applications (1), recycled or reused material (2), and proposals for novel materials (3) for which there was no evidence of recurrent use in this field. For this purpose, a multi-criteria decision analysis is developed considering several key indicators selected under sustainability criteria. To carry out this analysis, the indicators were experimentally quantified through laboratory tests, while the importance given to each indicator was evaluated through bibliographic references and consultation with experts in the sector. Results showed that the substrate including reused or recycled material (S2) generally provides better performance, and highlighted the suitability of combinations with both woven polypropylene geotextile (G1) and non-woven geotextile made using recycled polypropylene (G2). Graphical abstract: Image 1 Highlights: A methodology to evaluate the substrate layer and the geotextile was designed. Three types of substrates and three geotextiles were analysed. Geotextiles and substrates were combined and nine composite sections were studied. Among other solutions, a novel one, based on recycled phenolic foam, was studied. Composite sections including reused or recycled material show higher performance.